SAP modul pro platby faktur s využitím QR kódů - Švancar, Boris (Vysoké učení technické v Brně. Fakulta informačních technologií, 2014)
Práce se věnuje kódováni platebních údajů faktur do QR kódů podle standardu by square. Představený je zde systém SAP, postup kódování dat do QR kódů a standard PAY by square. Dle standardu je vytvořen funkční modul pro systém SAP v jazyce ABAP s využitím formulářů SmartForms, který umožňuje tyto QR kódy generovat na fakturu. Modul je následně podroben testování. Závěr práce tvoří zhodnocení dosažených výsledků a popis případného dalšího rozvoje.

The master's thesis deals with encoding payment data invoices into QR codes in accordance with the by square standard. The SAP system along with a process of encoding data into QR codes and by square PAY standard is introduced in my thesis. In compliance with the standard function module is designed for the SAP system which is in the ABAB language, using Smartforms form allowing the QR codes to generate the invoice. The module is then subjected to testing. The results are evaluated in conclusion of the master's thesis and a description of potential further development is assessed as a final step.
SAP Modul for Encoding Invoices to QR Codes
Keywords: SAP; ABAP; SmartForms; QR kód; platba faktur; internetbanking; standard by square; PAY by square; XML; CRC32; komprese LZMA; konverze Base32hex; SAP; ABAB; SmartForms; QR code; invoice payments; by square standard; PAY by square; XML; compression LZMA; conversion Base32hex